Performance and metabolism of early lactation dairy cows receiving doses of calcium salts of palm oil supplemented or not with Lysolecithin - Machado, Djonatan (2020)
The objectives were to evaluate the effects of supplementation with doses of calcium salts of palm oil with or without Lysolecithin on production responses, nutrient digestibility, energy intake and balance, metabolic responses, and ruminal responses of early lactation dairy cows on dry lot. Forty-four early lactation Holstein cows (Holstein or ¾Holstein ¼ Jersey), 28 multiparous and 16 primiparous (average ± SD at the beginning of the experiment; DIM = 20 ± 4 and 20 ± 9; milk yield = 25 ± 3.7 kg and 19 ± 2.5 kg; BW = 553 ± 11 kg and 444 ± 14 kg, respectively), were used in a randomized complete block design in the performance trial and three ruminal cannulated cows in a replicated 3 x 3 Latin square design, in the metabolism trial. Cows were fed corn silage ad libitum plus 9 kg of concentrate (as fed), provided individually, containing calcium salts of palm oil (CSPO) associated or not with Lysolecithin (1% of Lysoforte®, , Kemin Industries, Inc. with 98% of Lysolecithin). The trial lasted 90 days and started between week 3 and 4 postpartum. The treatments were control (concentrate with 400g of CSPO without Lysolecithin (CSPO-400); and concentrates with three levels of CSPO with 1% Lysolecithin (CSPOL), 280g, 340g and 400g. Preplanned contrasts were made to determine the effects of Lysolecithin (Lyso), comparing the treatments with 400g of CSPO supplementation, and linear (L) or quadratic (Q) effect of increasing CSPO with Lysolecithin (280, 340 and 400g of CSPOL) in the performance trial and effect of Lysolecithin (Lyso) and effect of the CSPO with Lysolecithin increase (280g to 400g of CSPOL); (D), in the metabolism trial. For the performance trial, dry matter intake, intake of dietary nutrients, and apparent digestibility of nutrients were measured twice during the experimental period (at 35 and 65 DIM). These variables were not different between treatments CSPO and CSPOL-400. The levels of CSPOL tended to cause a linear decrease on the intakes of DM and OM, and a linear increase on the intake and apparent digestibility of FA. There were no treatment effects on yields of milk, milk components and on cumulative milk yield. The treatment with CSPOL-400 tended to cause a decrease on milk fat content, and an increase on MUN compared with CSPO-400, while levels of CSPOL caused a linear decrease on milk fat content and on MUN content. Cow BW, BW changes and BCS were not affected by feeding Lysolecithin and levels of CSPOL. Feeding Lysolecithin for dairy cows fed 400 g of inert fat had no effect on energy intake, energy output, energy balance and efficiency of energy utilization. During the treatment period, there was no effect of Lysolecithin on plasma concentrations of total protein, insulin, NEFA and urea. However, supplementing Lysolecithin increased plasma glucose concentration. Levels of CSPOL caused a linear increase on plasma glucose concentration. For the metabolism trial, feeding Lysolecithin to lactating dairy cows fed 400g of inert fat had no effect on intake and digestibility of DM and nutrients, on rumen pH, total VFA, molar proportions of acetate, butyrate and isobutyrate, on C2:C3 ratio and on rumen NH3-N concentration, but tended to increase rumen propionate and increased rumen valerate. We conclude that the Lysolecithin had no effect on nutrient intake and total-tract digestibility, metabolic-hormonal profile, energy partitioning, milk yield and on most milk component contents, BW and BCS of early lactating cows fed 400g of CSPO. In addition, in the presence of Lysolicithin, increasing CSPO supplementation from 280 to 400g did not improve cow performance.